Unpopular Culture Transforming the European Comic Book in the 1990s - Beaty, Bart 1969- (Studies in Book and Print Culture, 2019)
In the last fifteen years or so, a wide community of artists working in a variety of western European nations have overturned the dominant traditions of comic book publishing as it has existed since the end of the Second World War. These artists reject both the traditional form and content of comic books (hardcover, full-colour 'albums' of humour or adventure stories, generally geared towards children), seeking instead to instil the medium with experimental and avant-garde tendencies commonly associated with the visual arts. Unpopular Culture addresses the transformation of the status of the comic book in Europe since 1990. Increasingly, comic book artists seek to render a traditionally degraded aspect of popular culture un-popular, transforming it through the adoption of values borrowed from the field of 'high art.' The first English-language book to explore these issues, Unpopular Culture represents a challenge to received histories of art and popular culture that downplay significant historical anomalies in favour of more conventional narratives. In tracing the efforts of a large number of artists to disrupt the hegemony of high culture, Bart Beaty raises important questions about cultural value and its place as an important structuring element in contemporary social processes